Fault diagnosis of induction motors - Faiz, Jawad; Ghorbanian, Vahid; Joksimović, Gojko (Institution of Engineering and Technology, 2017)
This book is a comprehensive, structural approach to fault diagnosis strategy. The different fault types, signal processing techniques, and loss characterisation are addressed in the book. This is essential reading for work with induction motors for transportation and energy.
Keywords: Electric motors, Induction.; Fault location (Engineering); elektronické knihy; electronic books